Studies in the biosynthesis of the hormones of the thyroid gland. - Wilson, Brian Denis (Division of Physiological Sciences, 2020)
This project was undertaken in order to elucidate two important problems in Thyroid Biochemistry namely, the kinetics of labelling of tyrosine and monoiodotyrosine (MIT) and the pathways of synthesis of triiodothyronine (T3 ) and thyroxine (T4 ).